The Role of Corporate Governance in Moderating the Relationship between Tax Risk and Leverage on Firm Value - Nur Rohmah Zainul Fitri; Hexana Sri Lastanti (Eduvest - Journal of Universal Studies, 2024)
This study aims to examine the effect of tax risk and leverage on firm value, with corporate governance acting as a moderating variable. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2017 to 2021. By using a purposive sampling method, the study selects companies based on specific criteria, including those that have consistently published audited financial statements in Rupiah. The independent variables in this study are tax risk and leverage, while corporate governance serves as the moderating variable. The dependent variable, firm value, is measured using Tobin’s Q, a widely accepted indicator. The analysis is conducted through panel data regression, with the Fixed Effect Model used to estimate the relationships among the variables. The results reveal that tax risk positively affects firm value, suggesting that effective tax management can enhance firm value by stabilizing cash flow and reducing tax penalties. However, leverage has a negative effect on firm value, as high debt levels increase financial risk, which may deter investors. Corporate governance significantly moderates the relationships, enhancing the positive effect of tax risk and reducing the negative impact of leverage on firm value. These findings underscore the importance of sound corporate governance practices in maintaining firm value by managing financial and tax-related risks. The study provides valuable insights for policymakers and corporate management on improving governance structures to optimize firm value.